Design of Modified Chicken Feather Retractor Machine - Mudin, Hatimi; Bagu, Chicha; Nor, Fethma M (Journal of Applied Science, Engineering and Technology, 2021)
The demand for poultry products is seen increasing from year to year. This is a good thing for local chicken entrepreneurs. But the task of plucking chicken feathers is time-consuming and tiring. The production of machines to help simplify the process of removing chicken feathers is seen as a necessity for these small and medium industrial entrepreneurs. This is why we focus on producing chicken feather retractor machines (CFRM) that are capable of processing up to five chickens at once. This machine is portable and easy to move around and supported by four wheels that can be locked to ensure stability. This machine can perform effectively to remove feathers using friction concept between the chicken and the plucker fingers rubber which attached around the drum. The machine also environmentally friendly by filtering the feather from scattered everywhere and only allow water to come out. The result shows that this machine operates under the motor powered with 115.13 rpm with the rotating plate area is 0.166 m2 and drum volume of 0.158 m3. This machine managed to remove the feathers of up to five chickens within 30 seconds to 60 seconds.